Physical Modeling Of Multi Quantum Well (MQW) P-I-N InGaAs InAlAs Solar Cell - Muniappan, Logaruthran (Universiti Sains Malaysia, 2018)
Multi Quantum Well Solar Cell is an advanced improvement of the conventional solar cell to overcome problem encounter in a normal solar cell. In a normal solar cell, the photon energy absorption rate is low causing the electron absorption rate to be low directly. A lower electron absorption results in a smaller value of current and voltage generated. Therefore, the introduction of multi-quantum well structure in the intrinsic region of the solar cell was introduced to allow more electron is absorbed and increase the efficiency of the solar cell. The proposed method in this project is to use III-V material which is Indium Gallium Arsenide (InGaAs) and Indium Aluminium Arsenide (InAlAs) as its quantum well material. due to its greater band-gap energy. In addition, to increase the efficiency of the solar cell, in this project, the number of quantum well present and depth of the quantum well varies to study the performance of the multi-quantum well solar cell. The modeling of the multi quantum well solar cell is done by using the Silvaco TCAD software. The result collected in this project is to rate the performance of MQW solar cell are open circuit voltage, short circuit current, fill factor, efficiency, recombination rate, band-gap energy and spectral response. In this research, the increase of the quantum well number and depth, increases the short circuit voltage, efficiency and fill factor. The value of the open circuit voltage was constant even though the quantum well number and depth varies. Finally, to achieve a greater solar cell output value, the number of the quantum well should be high and the quantum well depths should be deeper in order to ensure more absorption of the electron.